2011
DOI: 10.1021/nn201092p
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Inducing Property of Atomically Thin Graphene Oxide Sheets

Abstract: Graphene oxide (GO), the new two-dimensional carbon nanomaterial, is extensively investigated for potential biomedical applications. Thus, it is pertinent to critically evaluate its untoward effects on physiology of tissue systems including blood platelets, the cells responsible for maintenance of hemostasis and thrombus formation. Here we report for the first time that atomically thin GO sheets elicited strong aggregatory response in platelets through activation of Src kinases and release of calcium from intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
208
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(223 citation statements)
references
References 52 publications
8
208
1
4
Order By: Relevance
“…Platelets contribute to 95% of circulating amyloid precursor protein that releases Aβ into circulation. We have recently demonstrated that the Aβ active fragment containing amino acid sequence 25-35 (Aβ [25][26][27][28][29][30][31][32][33][34][35] ) is highly thrombogenic in nature and elicits strong aggregation of washed human platelets in a RhoA-dependent manner. In this study, we evaluated the influence of fibrinogen on Aβ-induced platelet activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets contribute to 95% of circulating amyloid precursor protein that releases Aβ into circulation. We have recently demonstrated that the Aβ active fragment containing amino acid sequence 25-35 (Aβ [25][26][27][28][29][30][31][32][33][34][35] ) is highly thrombogenic in nature and elicits strong aggregation of washed human platelets in a RhoA-dependent manner. In this study, we evaluated the influence of fibrinogen on Aβ-induced platelet activation.…”
mentioning
confidence: 99%
“…Intriguingly, Aβ failed to induce aggregation of platelets suspended in plasma but not in buffer. Fibrinogen brought about dose-dependent decline in aggregatory response of washed human platelets elicited by Aβ [25][26][27][28][29][30][31][32][33][34][35] , which could be reversed by increasing doses of Aβ. Fibrinogen also attenuated Aβ-induced platelet responses such as secretion, clot retraction, rise in cytosolic Ca +2 and reactive oxygen species.…”
mentioning
confidence: 99%
“…32 Exposure of PC12 cells to grapheme resulted in mitochondrial injury that was dose and shape dependent. 31 Exposure of blood platelets to rGO caused a strong cumulative response and extensive pulmonary thromboembolism 33 and, similarly, exposure of alveolar macrophages and epithelial cells to grapheme generated ROS and led to inflammation, apoptosis, and an increased rate of mitochondrial respiration. 34 Our previous studies showed that both GO and rGO induced oxidative stress-mediated cell death in various cell lines, including human breast cancer cell lines MDA-MB-231 28 and MCF-7, 5 and human ovarian cancer cell line A2780.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of albumin and globulin, the urea levels in the blood, and all hematology markers were also unchanged. 27,33,176 Singh et al 182 found that GO could induce extensive pulmonary thromboembolism in mice. Few-layer graphene with diameters up to 25 μm induced high levels of inflammation in the mouse lung.…”
mentioning
confidence: 99%